Assessment of knowledge and attitude towards hpv and hpv vaccination among students at Institut Pendidikan Guru (IPG) Kampus Kota Bharu - Mansor, Noor Asyikin (Universiti Sains Malaysia, 2015)
Human Papillomavirus (HPV) is a major factor for cervical cancer. The cervical cancer was ranked as the second most common cancer that occurs among women worldwide. The routine HPV vaccination to combat the disease is not widely available in most developing countries. However, in Malaysia there was an initiative that taken to reduce the spread of HPV infection which is by offered free HPV vaccination to 13 years old females. The most effective ways to implement this by organizing a national school based vaccination program. Teachers are groups that may have good influence in the success of the program therefore important to provide information on them. The purpose of this study to assess the knowledge and attitude towards HPV and HPV vaccination among students at Institut Pendidikan Guru (IPG) Kampus Kota Bharu which was involving students that going to be teachers in the future. This research was done to determine mean difference between selected demographic data with mean knowledge score as well as the mean difference between levels of knowledge with mean attitudes score towards HPV vaccination. This cross sectional study was carried out to 89 participants who selected through convenience sampling at IPG Kampus Kota Bharu. Both male and females students that was a first year students were included in this study. Self administered questions was distributed which consists of 3 parts. Part A is a demographic data, Part B is a Knowledge on HPV and HPV vaccine while Part C is assessing Attitudes towards HPV vaccination. The data obtained was analyzed by using SPSS version 21.0 by using One Way Anova statistical test to determine the mean difference of the variable involved. This study showed that the level of knowledge is 41.6% of them have poor knowledge levels while there was only 11.2% had good knowledge and the remaining had an average knowledge with 47.2%. However, there were 43.8% of participants had a positive attitude. The demographic data (parents’ educational level) found to have significant mean difference with mean knowledge score with p value= 0.030 and 0.042 for mother and father education level respectively. Furthermore, there was also a significant mean difference between the level of knowledge with mean attitude score with p value= 0.001. As a result of the findings although they have low levels of knowledge but majority of them have positive attitude regarding HPV vaccination. This positive attitude will lead to intention to get HPV vaccination and they need to be provided with health education and adequate information regarding HPV infection, HPV vaccine and HPV vaccination to make sure an effective prevention to reduce the burden of cervical cancer incidence.